Communicatio In Sacris Berbagi Kasanah Rohani Medium Membangun Persaudaraan di Antara Umat Kristiani Analisa Sejarah, Doktrin dan Iuris - I Ketut Gegel (Sekolah Tinggi Widya Sasana, 2020)
In this paper, the author studies of Communicatio in Sacris as an act of sharing sacraments among Christians. This study begins with the author's observation regarding of relation among Christians at this time. In the past centuries, many dissensions happened and large communities were separated from full communion with Catholic Church. Each excludes others to take part in its own liturgy. However, it should be kept in mind, that unity which Christ willed, stood at the very heart of the Church’s mission. At every era, there have been figures who do not only defend the Church but also open the Church to other Christians, especially, in her liturgical services. It has begun a long the history of the Church. It is sufficient to simply to mention two of them. In 1244 Innocent IV allowed Dominicans to minister separated Christian communities by sharing the Eucharist with them. In modern age, John XXIII who led the 2nd Vatican Council has brought Catholic Church even more open toward other Churches, giving a wide possibility to share sacraments with non Catholic. The purpose of all these actions is for the goodness of souls. The method used in this article is a qualitative research, by analyzing the Church view of communicatio in sacris. The author analyzed the Church documents: 2nd Vatican Council, Canon Law and other sources, including digital sources to support the analysis. From this study, the author found out that communicatio in sacris in its strict meaning means to share sacraments amongs Christians that becomes an instrument to foster fraternity among Christians.